PENENTUAN TITIK RAWAN KECELAKAAN (BLACK SPOT) PADA RUAS JALAN NASIONAL PALEMBANG – INDRALAYA (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2022)
Traffic accidents are one of the biggest causes of death in Indonesia. An accident-prone location is a highaccident rate with the incidence of repeated accidents in a relatively the same space and period caused bya specific cause (Pd-T-09-2004-B). Based on data from Lakalantas Polres Ogan Ilir (2018), trafficaccidents in Ogan Ilir Regency are ranked second below Palembang among all districts in South SumatraProvince, with 257 incidents, 101 deaths and 394 injuries. On the Palembang-Indralaya road segment in2018, there were accidents with 80 cases, and 27 people died. For this reason, it is necessary to analyzethe accident-prone points (Black spot) on the Palembang - Indralaya National Road Section. The dataused to determine the Black spot point is traffic accident data within four years using the AccidentEquivalent Number (AEK) method. The analysis of accident data from 2015 - 2019 contained 14 Blackspot points on the Palembang - Indralaya national road with various levels of victim injuries.